Advanced HVOF-Sprayed Carbide Cermet Coatings as Environmentally Friendly Solutions for Tribological Applications: Research Progress and Current Limitations - Basma Ben Difallah; Yamina Mebdoua; Chaker Serdani; Mohamed Kharrat; Maher Dammak (Technologies, 2025)
Thermally sprayed carbide cermet coatings, particularly those based on tungsten carbide (WC) and chromium carbide (Cr3C2) and produced with the high velocity oxygen fuel (HVOF) process, are used in tribological applications as environmentally friendly alternatives to electroplated hard chrome coatings. These functional coatings are especially prevalent in the automotive industry, offering excellent wear resistance. However, their mechanical and tribological performances are highly dependent on factors such as feedstock powders, spray parameters, and service conditions. This review aims to gain deeper insights into the above elements. It also outlines emerging advancements in HVOF technology—including in situ powder mixing, laser treatment, artificial intelligence integration, and the use of novel materials such as rare earth elements or transition metals—which can further enhance coating performance and broaden their applications to sectors such as the aerospace and hydro-machinery industries. Finally, this literature review focuses on process optimization and sustainability, including environmental and health impacts, critical material use, and operational limitations. It uses a life cycle assessment (LCA) as a tool for evaluating ecological performance and addresses current challenges such as exposure risks, process control constraints, and the push toward safer, more sustainable alternatives to traditional WC and Cr3C2 cermet coatings.